Authors' Rebuttal to Paper by Ramaswami and Lucantoni - Gross, Donald; Harris, Carl M. (Management Science, 1979)
Authors' Rebuttal to Paper by Ramaswami and Lucantoni (Ramaswami, V., David M. Lucantoni. 1979. Note—On the merits of an “approximation” to the busy period of the GI/G/1 queue. Management Sci. 25 285–289).